Rebel girl : my life as a feminist punk - Hanna, Kathleen, 1968- (Ecco, 2024)
"An electric, searing memoir by the original rebel girl and legendary front woman of Bikini Kill and Le Tigre. Hey girlfriend I got a proposition, goes something like this: Dare ya to do what you want. Kathleen Hanna's rallying cry to feminists echoed far and wide through the punk scene of the '90s and beyond. Her band Bikini Kill embodies this iconic time, and today her personal yet feminist lyrics on anthems like "Rebel Girl" and "Double Dare Ya" are more powerful than ever. But where did this transformative voice come from? In Rebel Girl, Hanna's raw and insightful new memoir, she takes us from her tumultuous childhood home to her formative college years in Olympia, Washington, and on to her first years on tour, fighting hard for gigs and for her band. As Hanna makes clear, being in a "girl band," especially a punk girl band, in those years was not a simple or safe prospect. Male violence and antagonism threatened at every turn, and surviving as a singer who was a lightning rod for controversy took limitless amounts of determination. But the relationships she developed during those years buoyed her-including with her bandmates, Tobi Vail, Kathi Wilcox, and Johanna Fateman; her friendships with Kurt Cobain and Ian MacKaye; and her introduction to Joan Jett- were all a testament to how the punk world could nurture and care for its own. Hanna opens up about falling in love with Ad-Rock of the Beastie Boys and her debilitating battle with Lyme disease, and she brings us behind the scenes of her musical growth in her bands Le Tigre and The Julie Ruin. She also writes candidly about the Riot Grrrl movement, documenting with love its grassroots origins but critiquing its later exclusivity. In an uncut voice all her own, Hanna reveals the hardest times along with the most joyful-and how it continues to fuel her revolutionary art and music"--